Vocation of the Artist - Ewens, Thomas (Philosophy & theology, 1992)
Macmurray’s understanding of the vocation of the artist and how it is that the artist can create and be are discussed in two sections. In the first, which is subdivided into four smaller sections, presents a discussion of what Macmurray means by ‘contemplation’. The second is devoted to the artist’s role in helping to bring about ‘the Kingdom of the Future’.